Exploring the impact of the check-in/check-out (CICO) behavior intervention on teacher-student relationships and teacher perception of students with challenging behaviors - Delay, Jenna (Kansas State University, 2022)
This qualitative case study evaluates the impact of the Tier 2 behavior intervention known as Check-In/Check-Out (CICO) on student-teacher relationships and their perceptions of each other, especially in the case of students experiencing behavioral challenges, such as anti-social behavior in the classroom, that typically results in removing the student from the learning environment. The theoretical frameworks guiding the study are educational equity theory, transactional theory, and self-efficacy theory. The research design focused on four student and teacher participant pairings in grades 6, 7, and 8 attending a rural middle school in the Midwest of the United States. The student participants were recommended for participation by the grade-level teacher teams based on data in the areas of attendance, discipline, grades, hallway passes, and behavior screeners. The pairings completed a relationship survey and experienced an interview with the researcher prior to, during, and at the end of the CICO intervention. The following research questions were explored: (1) What is the effect of positive relationships between student and teacher, specifically at the middle school level, and in what ways does this relationship impact the goal of educational equity for all students regarding access to the curriculum?; (2) In what ways, if any, does the use of the CICO intervention impact teachers’ perceptions of students with behavioral challenges?; and (3) How does the use of the CICO intervention impact students’ perceptions of the teachers who implement this intervention? The findings suggest that the CICO intervention has potential to allow for the structured, purposeful growth of positive student-teacher relationships that produce students who are better prepared for their educational futures.
Keywords: CICO; Teacher-student relationships; PBIS; Behavioral challenges